On the properties of blocks of terms of the series 1k kx - Telyakovskii, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We investigate the decomposability of the series 1k kx into blocks such that the sum of the series formed of the moduli of these blocks belongs to the spaces L^p[0, π] or the spaces L^p[0, π] with weight x^-γ,γ < 1.